2009
DOI: 10.4081/827
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of transcription sites at the electron microscope

Abstract: In order to localize at EM level the sites of transcription of both pre-mRNA and pre-rRNA, we have detected the DNA/RNA hybrid molecules and m3Gcapped structures by means of specific antibodies after short bromo-uridine (BrU) incorporation. In addition, the sections have been stained by a selective RNA stain, terbium citrate. Our data indicate that perichromatin fibrils incorporate BrU and are labeled by the anti-hybrid probe; this supports the idea that they are the pre-mRNA transcription sites. On the contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
(35 reference statements)
0
11
0
1
Order By: Relevance
“…Previous experiments (Trentani et al 2007) demonstrated that penetration of antibodies in these conditions does not damage the cell both in terms of structural preservation and functionality (e.g. incorporation of BrU, Trentani et al 2003). However, it is not clear by which mechanism the antibodies reach the nucleus, although this does not create major problems to the cell functionality (Trentani et al 2003).…”
Section: Treatment For Atp Depletionmentioning
confidence: 94%
“…Previous experiments (Trentani et al 2007) demonstrated that penetration of antibodies in these conditions does not damage the cell both in terms of structural preservation and functionality (e.g. incorporation of BrU, Trentani et al 2003). However, it is not clear by which mechanism the antibodies reach the nucleus, although this does not create major problems to the cell functionality (Trentani et al 2003).…”
Section: Treatment For Atp Depletionmentioning
confidence: 94%
“…Immunolabelled ultrathin sections were stained either with the EDTA method (Bernhard, 1969) to visualize RNP constituents, or with terbium citrate (Biggiogera and Fakan, 1998;Trentani et al, 2003) for selective RNA staining; Epon sections were conventionally stained with uranyl-lead. All samples were observed in a Zeiss EM 900 electron microscope operating at 80 kV.The gold grain contrast was digitally enchanced on the scanned micrographs using Adobe Photoshop.…”
Section: Methodsmentioning
confidence: 99%
“…The entire IC is separated from the more condensed interior of chromatin domains and/or higher-order chromatin fibers by a thin (,200 nm) layer of rather decondensed chromatin, termed the perichromatin region (PR) (Fakan and van Driel 2007). EM evidence has supported the view that the PR topographically represents the utmost periphery of a given chromatin domain bordering the IC and functionally represents the major nuclear subcompartment for transcription, cotranscriptional RNA splicing (Fakan and Bernhard 1971;Cmarko et al 1999;Trentani et al 2003), as well as DNA replication and possibly also DNA repair (Solimando et al 2009). Transcription yields perichromatin fibrils, which are generated in the PR as nascent pre-mRNA transcripts of single genes complexed with hnRNPs and are served by nearby speckles with factors for cotranscriptional splicing.…”
Section: Models Of Nuclear Architecture: Open Questions and Experimenmentioning
confidence: 99%